Da descrição à conservação : espécies raras ou pouco conhecidas de peixes das bacias dos rios Tocantins e Paraná - Vitorino Júnior, Oscar Barroso (2019)
A major challenge for conservation biology is to explain why some species are more likely to be endangered than others. Functional diversity is one of the most effective theoretical tools to explain the functioning of ecosystems, that is, whether species will adapt to changes or not, and may indicate traits that are more prone to extinction. Given the Brazilian biodiversity, the ecosystem services provided by it and the impacts it may suffer, there is an urgent need for a discussion on the methods and sources of information used for this assessment. Therefore, this thesis is divided into three studies. In the first study, a literature review was carried out on the different methodologies used for the classification of “rare species”, a very controversial and little studied topic. In the second study, the taxonomic indeterminacy of fish studies in the Neotropical region between 1991 and 2018 was investigated, relating the indeterminacy by year, basin and families. In this context, in the last study, precisely with the need to investigate the metacommunities of tropical systems, patterns of functional rarity in fish assemblages in a section of the Upper Rio Tocantins, Amazon Basin and the Upper Paraná River Floodplain were analyzed. last book excerpt of dams of this water system. Thus, this study will contribute to the understanding of the different patterns at the community level.